Review on niobium-based chalcogenides for electrochemical energy storage devices: Application and progress. (November 2019) - Zhang, Xikun; Peng, Na; Liu, Tingting; Zheng, Runtian; Xia, Maoting; Yu, Haoxiang; Chen, Shi; Shui, Miao; Shu, Jie
Abstract: Electrochemical energy storage devices are currently an ideal tool to meet the energy needs of the people. It has been certified that niobium-based chalcogenides are generally used as the electrode materials for electrochemical energy storage devices due to their unique physical and chemical properties. This review summarizes the different synthesis methods and applications about the various niobium-based chalcogenides. In addition, in view of the existing problems of the niobium-based chalcogenides, many modification methods to improve the electrochemical properties of electrode materials are summarized, such as coating conductive matrixes, preparing composite materials, preparing porous or nanometer materials, and doping hetero atoms, etc. Finally, while summarizing the progress in recent years, the current bottlenecks and possible development directions in the future have also been proposed. Graphical abstract: Image 1 Highlights: Research progress of Nb-based chalcogenides in electrochemical energy storage is summarized. The shortcomings of Nb-based chalcogenides as electrode materials are presented. The measures to improve the performance of Nb-based chalcogenides are summarized.